Developing a consolidated research framework for clinical allied health professionals practising in the UK - Jennifer Harris; Kate Grafton; Jo Cooke (BMC, 2020)
Abstract Background Allied Health Professionals (AHPs) form a significant part of the healthcare workforce and have great potential to improve services through research and research-informed practice. However, there is a lack of tradition in research embedded in practice in these professional groups. Barriers include clinical caseload pressures, a lack of sustainable training and consequent lack of confidence in practitioners. Practice managers are ill-equipped to monitor and guide staff research development. The modern healthcare system is a multi-disciplinary environment focused on the needs of the patient. A common framework across all AHP disciplines, offering equality in research knowledge and skills and shared language, might be helpful in planning and developing clinical career pathways. Our aim is to develop a consolidated research framework to help AHPs to plan and guide research activity throughout their career. Methods The study was conducted in three phases. Phase one identified existing AHP research frameworks (AHPRF) through expert consultations and literature searches. Phase two involved framework analysis of the AHPRFs to develop a single consolidated framework. Phase three included a workshop with experts to validate and adapt the framework for practice. Results Nineteen AHPRFs were identified. A consolidated framework was shaped by analysis of the AHPRFs resulting in a consolidated framework of eight sections, each containing a series of statements. Each section relates to an analytic theme within the framework analysis, and the statements were based on sub-categories of themes. The final framework was further shaped by the phase three workshop into a set of 'stem' statements that can be adapted to reflect different levels of expertise and the inclusion of a set of guiding principles developed through expert consultation. Conclusion The consolidated framework was entitled 'Shaping Better Practice Through Research: A Practitioner Framework' by stakeholders, thus emphasising its ambition to embed research activity into practice. It instigates a new perspective within AHP research by offering practitioners and managers a tool that can be applied across public, private, and voluntary settings for AHPs in all disciplines. Its ambition is to develop capacity in the AHPs that can undertake research to improve services and the health of service users.